Minutes of General Council (extract)
017a-0051-001 Extract from G.C. Minutes 22nd June 38. (g) Second Anniversary of the Spanish Rebellion. It was explained that any locality that wanted to run a demonstration on the second anniversary of the Spanish Rebellion would get all the help the Head Office could give. 292/946/17a/51